Reducing Defects Number of Ampoule by Considering Expected Failure Cost At Quality Control Department of PT. X - Darmansyah Yudi; Hery Hamdi Azwir (President University, 2018)
PT. X is producing pharmaceutical packaging that made by glass tube as the raw material of the product; this study took ampoule as the sample. During the production process which is in the quality inspection, the operator found many defect products of ampoule such as crack 32%, glass particle 30%, deformation 14%, scratches 11%, air bubbles 10%, and printing 3%. Multi-Attribute Failure Mode Analysis (MAFMA) is one of them used to eliminate or reduce the causes of failure in order to prevent the repeating failure. The attributes became the criteria level in a hierarchy structure and the potential causes as alternative level. PT. X case study showed on crack failure that weight of severity, occurrence, detectability, and expected cost respectively are 0.3498, 0.0659, 0.1322, 0.4521. The weight of potential failure cause which is the storage room temperature not suitable (Cause A) is 0.2813. After the implementation of defect causes prevention, the percentage of defect reduction is 45% or about 43 units. In the average, the reduction of the defect is 37% or 36 units.Keywords: Quality Checking, Nonconformity, Defected Products, Failure Mode and Effect Analysis (FMEA), Multi-Attribute Failure Mode Analysis (MAFMA), Analytical Hierarchy Process (AHP).